Exposure to Respirable Crystalline Silica in the GB Brick Manufacturing and Stone Working Industries. Issue 2 (9th January 2019) - Baldwin, Peter E J; Yates, Timothy; Beattie, Helen; Keen, Chris; Warren, Nicholas
Abstract: The aim of this work was to benchmark respirable crystalline silica (RCS) exposures in brick manufacturing and stone working sectors in Great Britain. This will contribute to a larger programme of work, which will be used to better understand the role of health surveillance in preventing the development of further cases of silicosis and chronic obstructive pulmonary disease. This work was undertaken by means of site visits to measure RCS and respirable dust exposures and assess exposure controls. In addition, historic exposure reports from the sites were collated to allow assessment of exposure trends. The survey, which was conducted in 20 sites (10 from each sector), found that in both sectors over 20% of the measured exposures exceeded the UK RCS 8-hour time-weighted averaged workplace exposure limit (WEL) of 0.1 mg/m 3 . In the stone sector over 40% of the 8 h time-weighted average RCS exposures were above the RCS WEL compared to 20% in the brick manufacturing sector. In the stone sector, 61% of RCS exposures where water suppression was present exceeded the RCS WEL. This indicates that a variety of exposure controls will be required to control RCS exposures, including respiratory protective equipment (RPE). The use of RPE in situations where RCS exposure exceeded the RCS WEL was more prevalent in stone working than in the brick sector. There were differences associated with RPE and the use of other exposure controls in both sectors. The contextual information in historic consultant's exposure reports was generally limited, with exposure controls either not mentioned or not fully described. This affects the usefulness of exposure monitoring to dutyholders. This work will provide information on exposures allowing construction of lifetime exposure estimates for use in analysis of the health effects data. A second survey to the sites is planned to determine how exposures have altered.